### Author Topic: LEC0201-Retest-ALT-Y-Question1  (Read 885 times)

#### RunboZhang

• Sr. Member
•    • Posts: 51
• Karma: 0 ##### LEC0201-Retest-ALT-Y-Question1
« on: October 23, 2020, 04:18:51 PM »
$\textbf {Problem:} \\\\$
$\text{(a) Find integrating factor and then a general solution of ODE} \\$
$\begin{gather} (1+xy+y^{2}) + (1+xy+x^{2})y' = 0 \end{gather}$
$\text{(b) Also, find a solution satisfying y(1) = 1}\\\\$

$\textbf{Solution: } \\\\$
$\text{(a):}\\\\$
$\text{We have:}$

\begin{gather} \begin{aligned} M_y = x+2y \\\\ N_x = y+2x \end{aligned} \end{gather}

$\text{Since} M_y \ne N_x \ \text{, thus equation is not exact.}$

\begin{gather} \begin{aligned} \frac{N_x - M_y}{M \cdot x - N \cdot y} &{}= \frac{y+2x-x-2y}{x+x^{2}y+xy^{2}-y-xy^{2}-x^{2}y} \\\\ &{} = \frac{x - y}{x - y} \\\\ &{} = 1 \end{aligned} \end{gather}

$\text{Now, we have our integrating factor } \mu \ \text{computed as follow: }$

\begin{gather} \begin{aligned} \mu &{} = e^{\int {1} \, dxy} \\\\ &{} = e^{xy} \end{aligned} \end{gather}

$\text{Now multiplying the original equation with our integrating factor, we have: }$

\begin{gather} \begin{aligned} e^{xy} + e^{xy} \cdot xy + e^{xy} \cdot y^{2} + (e^{xy} + e^{xy} \cdot xy + e^{xy} \cdot x^{2})y' = 0 \end{aligned} \end{gather}

$\text{Lastly, solve for general solution F(x,y): }$

\begin{gather} \begin{aligned} F(x,y) &{} = \int_{0}^{x} (e^{xy} + e^{xy} \cdot xy + e^{xy} \cdot y^{2}) \, dx + h'(y) \\\\ &{} = x \cdot e^{xy} + y \cdot e^{xy} = c \end{aligned} \end{gather}

$\text{(b):}\\\\$
$\text{By plugging in initial value condition, we have: }$
\begin{gather} \begin{aligned} y(1) = 1 \\\\ c = e + e = 2e\\\\ \implies x \cdot e^{xy} + y \cdot e^{xy} = 2e \end{aligned} \end{gather}